2004
DOI: 10.1126/science.1092734
|View full text |Cite
|
Sign up to set email alerts
|

Direct Activation of Bax by p53 Mediates Mitochondrial Membrane Permeabilization and Apoptosis

Abstract: The tumor suppressor p53 exerts its anti-neoplastic activity primarily through the induction of apoptosis. We found that cytosolic localization of endogenous wild-type or trans-activation-deficient p53 was necessary and sufficient for apoptosis. p53 directly activated the proapoptotic Bcl-2 protein Bax in the absence of other proteins to permeabilize mitochondria and engage the apoptotic program. p53 also released both proapoptotic multidomain proteins and BH3-only proteins [Proapoptotic Bcl-2 family proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
1,467
6
11

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 1,835 publications
(1,550 citation statements)
references
References 28 publications
66
1,467
6
11
Order By: Relevance
“…Importantly, however, expression of high amounts of p53 without additional DNA-damage did not induce apoptosis in NIH3T3 cells (Figure 4a, b), indicating that damage-induced activation of p53 is required for the pro-apoptotic effect. In accordance with our observation that higher p53 levels do not correlate with higher expression levels of p53 targets (see before), the higher p53 amounts in HA-p53 transfected and Cytosolic p53 accumulates in pre-apoptotic cells and correlates with Bax-activation Recent studies have linked non-transcriptional proapoptotic activities of p53 to a cytosolic or mitochondrial localization of the protein (Chipuk et al, 2003(Chipuk et al, , 2004Dumont et al, 2003;Mihara et al, 2003;Leu et al, 2004). To test whether such a non-transcriptional activity of p53 might account for 100 J/m 2 UV-induced apoptosis in NIH3T3 cells, we monitored differently irradiated NIH3T3 cells for the presence of cytosolic p53.…”
Section: Upregulation Of Bax and Pig3 Is Not Sufficient To Induce Aposupporting
confidence: 91%
See 4 more Smart Citations
“…Importantly, however, expression of high amounts of p53 without additional DNA-damage did not induce apoptosis in NIH3T3 cells (Figure 4a, b), indicating that damage-induced activation of p53 is required for the pro-apoptotic effect. In accordance with our observation that higher p53 levels do not correlate with higher expression levels of p53 targets (see before), the higher p53 amounts in HA-p53 transfected and Cytosolic p53 accumulates in pre-apoptotic cells and correlates with Bax-activation Recent studies have linked non-transcriptional proapoptotic activities of p53 to a cytosolic or mitochondrial localization of the protein (Chipuk et al, 2003(Chipuk et al, , 2004Dumont et al, 2003;Mihara et al, 2003;Leu et al, 2004). To test whether such a non-transcriptional activity of p53 might account for 100 J/m 2 UV-induced apoptosis in NIH3T3 cells, we monitored differently irradiated NIH3T3 cells for the presence of cytosolic p53.…”
Section: Upregulation Of Bax and Pig3 Is Not Sufficient To Induce Aposupporting
confidence: 91%
“…Further analysis assigned the pro-apoptotic activity of high amounts of activated p53 to cytosolic p53, which was able to trigger Bax-activation. Previous in vitro studies had already shown that cytosolic p53 can activate Bax in a transcription-independent manner analogous to that of BH3-only-proteins, and thereby lead to apoptosis (Chipuk et al, 2003(Chipuk et al, , 2004. Our data demonstrate for the first time the relevance of this mechanism in vivo.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations